1978
DOI: 10.1139/v78-302
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates in the γ-radiolysis of diraient sulfur compounds in dilute glass matrices

Abstract: Can. J. Chem. 56, 1856(1978).The optical spectra of the charged ions obtained from y-irradiation of dilute alkyl niercaptans, sulfides, and disulfides in a variety of dilute rigid glasses are measured at 77 K. The photochemical stability of these ions is determined. A new photochromic species has been found. It is derived from a niercaptan dimer cation and is analogous to the photochromic anion produced from alkyl disulfides. The results of y-radiation are compared to the uv photolysis of similar matrices, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Research works are mainly devoted to the stabilization of charged sulfides in dilute glass matrixes, the creation of Rydberg series, and state-selected ions in the gas phase by resonantly enhanced multiphoton ionization. [4][5][6][7][8] Photoexcited organic sulfides undergo different responses which can lead to bond scissions or ionization channels. The primary processes triggered by a UV excitation of liquid organic sulfides correspond to S-S or C-S bond scissions and yield multiple radicals such as methyl thiyl radical (CH 3 S • (A)) or thioformaldehyde (CH 2 S • (X)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research works are mainly devoted to the stabilization of charged sulfides in dilute glass matrixes, the creation of Rydberg series, and state-selected ions in the gas phase by resonantly enhanced multiphoton ionization. [4][5][6][7][8] Photoexcited organic sulfides undergo different responses which can lead to bond scissions or ionization channels. The primary processes triggered by a UV excitation of liquid organic sulfides correspond to S-S or C-S bond scissions and yield multiple radicals such as methyl thiyl radical (CH 3 S • (A)) or thioformaldehyde (CH 2 S • (X)).…”
Section: Introductionmentioning
confidence: 99%
“…Charge-transfer processes involving organic sulfur compounds are of particular interest in biology and chemistry because transient sulfide radical ions can alter or protect the functional properties of enzymatic complexes or proteins. During the past decade, the photochemistry of sulfur-containing molecules has received considerable attention. Research works are mainly devoted to the stabilization of charged sulfides in dilute glass matrixes, the creation of Rydberg series, and state-selected ions in the gas phase by resonantly enhanced multiphoton ionization. Photoexcited organic sulfides undergo different responses which can lead to bond scissions or ionization channels. The primary processes triggered by a UV excitation of liquid organic sulfides correspond to S−S or C−S bond scissions and yield multiple radicals such as methyl thiyl radical (CH 3 S • (A)) or thioformaldehyde (CH 2 S • (X)). These bond breakings can compete with ultrafast electron photodetachment processes.…”
Section: Introductionmentioning
confidence: 99%
“…Following 254 nm photolysis of matrix isolated C 2 H 5 SH in xenon at 77 K, Skleton and Adam detected thiyl radical, ethylthiyl radical (C 2 H 5 S) using electron paramagnetic resonance. Adam et al later observed the same product after photolysis of C 2 H 5 SH in various dilute glass matrices. Bhuin et al measured the VUV spectrum of solid C 2 H 5 SH.…”
Section: Resultsmentioning
confidence: 78%
“…Detailed discussions of the assignments and identifications are in the Supporting Information. Generally, assignments were made possible by virtue of earlier spectroscopic measurements in both cryogenic matrices and the gas phase. ,,, …”
Section: Resultsmentioning
confidence: 99%